The use of artificial neural networks to predict pure tone thresholds in normal and hearing- impaired ears with distortion product otoacoustic emissions - Kruger, J.J. (University of Pretoria, 2013)
Dissertation (MCommunication Pathology)--University of Pretoria, 2009.